Pengaruh Dosis Pupuk dan Tinggi Permukaan Air pada Budidaya Padi Varietas M70D dengan Media Pasir - Ridwan, Ridwan; Sholihah, Annisa Mar'atus; Amien, Elhamida Rezkia; Amin, Muhammad (abe.fp.unila.ac.id, 2023)
This study aims to obtain the most suitable combination of water table level and organic fertilizer dosage for the growth and production of M70D rice varieties in sand media. The tools used include glass pots with a thickness of 5 mm, digital scales, floats, pipes, sprayers, tape measure and ruler. The materials used were rice seeds of the M70D variety, husk charcoal, soil, river sand, water, granule organic ghally fertilizer, and liquid ghally organic fertilizer. The research method used was a factorial experiment in a completely randomized design with 2 factors, namely fertilizer dose (d) and water level (a) with each treatment repeated 3 times (U). The growth of rice plants (Oryza Sativa L.) variety M70D will be optimum if given a dose of 5 g of fertilizer in the vegetative phase. Whereas in the generative phase, it will be optimum with a 15 gr fertilizer dose. A water level of -1 cm below the surface had the best effect on plant height and number of leaves of Paddy (Oryza Sativa L.) variety M70D in the vegetative phase. Whereas in the generative phase, will be optimum with the water level of 0.5 cm. The application of a fertilizer dose of 15 g and a water level of 0.5 provides the most optimal effect for the growth and development of rice variety M70D. Keyword: Fertilizer, Glass, Paddy, Potted rice, Sand media.